Studi Literatur: Penerapan Model Pembelajaran Kooperatif Tipe Teams Games Tournament (TGT) untuk Meningkatkan Hasil Belajar Matemat-ika Siswa: A Review of Teams Games Tournament (TGT) Cooperative Learning Model to Improve Students’ Mathematics Learning Outcomes - Suliani, Mega; Kartika, Hendra; Ulfah, Fithria; Mutmainah, Siti (Journal of Research in Science and Mathematics Education, 2024)
Purpose: The objective of this study is to describe the efficacy of the Teams Games Tournament (TGT) learning model in enhancing student learning outcomes in mathematics. Methodology: To achieve this, the study employs a descriptive qualitative method combined with a systematic literature review approach. The data collection process involved a comprehensive examination of references, including scientific articles, research papers, and relevant books that address the application and impact of the TGT learning model. Findings: The Teams Games Tournament (TGT) is a dynamic pedagogical approach designed to actively engage students through structured discussions and collaborative competitions within a classroom setting. This method fosters a competitive yet cooperative environment that encourages students to participate fully in the learning process. The analysis of the collected data indicates that the TGT learning model has a positive impact on students' mathematical learning outcomes, leading to improved understanding and retention of mathematical concepts. Significance: Consequently, this study suggests that the TGT model could be a valuable tool for educators, offering an innovative solution to enhance mathematics instruction. By implementing this model, educators can create an active, enjoyable, and inclusive learning environment that caters to the diverse needs of all students, ultimately fostering a deeper appreciation and understanding of mathematics.